A Visit to the Hmong of Asia: Globalization and Ethnicity at the Dawn of the 21st Century. - Yang, Kou (Hmong Studies Journal, 2008)
This paper consists of observations made from my two and a half month visit to the Hmong in Thailand, Laos, Vietnam and China.(FN1) As such, it contains two parts. The first part is my observation of the Hmong in Asia and their common issues. The second part is a photo essay of the visit to the Hmong in Asia, covering issues discussed in the paper. Although I did visit other subgroups of the Miao, such as the Hmu in Guizhou and Qo Xiong(FN2) in Hunan, this paper covers only the Hmong, whom I hope will be better presented and discussed as a result of my work. Moreover, the Hmong live in all the above mentioned countries, whereas other subgroups of the Miao live only in China. This paper highlights the socio-economic conditions and educational experiences of the Hmong in the above mentioned countries. It also covers my observations of Hmong civic engagement and other aspects of their social and political lives in the respective countries. Reprinted by permission of the publisher.